VD_FINDINFO HC / 2013 / 613 vom 10. September 2013 - VD Tribunal cantonal (2013)
EXPULSION DE LOCATAIRE, EXÉCUTION FORCÉE, FRAISEN GÉNÉRAL | 106 al. 1 CPC (CH), 110 CPC (CH), 125 let. c CPC (CH), 319 let. b ch. 1 CPC (CH), 326 al. 1 CPC (CH)